Frequency of Anemia in Patients With Preterm Labour at Tertiary Care Hospital Quetta - Yousaf, Hira; Kasi, Zermin; Ashraf, Razmia; Rameen, Ifrah; Habib, Hafiza Ayesha; Kakar, Rabia Nasir (Biological and Clinical Sciences Research Journal, 2025)
Preterm labour is a major cause of neonatal morbidity and mortality, particularly in low-resource settings. Anemia, especially iron deficiency anemia, has been suggested as a modifiable risk factor contributing to preterm birth. Objective: To assess the frequency of anemia and its association with demographic and clinical variables in pregnant women with preterm labour. Methods: This descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Sandeman Provincial Hospital, Quetta, over a period of six months following ethical approval. A total of 146 pregnant women aged 18–40 years with preterm labour were enrolled using non-probability consecutive sampling. Data were collected using a structured proforma, including demographics, clinical findings, and hemoglobin levels. Anemia was defined as hemoglobin <11 g/dL. Results: Out of 146 participants, 90 women (61.6%) were found to be anemic. Severe anemia was noted in 6 cases (4.1%). Anemia was significantly more common in women aged <25 years (p = 0.03), those from rural areas (p = 0.04), those with lower socioeconomic status (p = 0.01), and those with limited education (p = 0.02). No significant association was found with parity (p = 0.16) or BMI (p = 0.09). Conclusion: It is concluded that anemia is a common finding in patients presenting with preterm labour, especially among socially and economically disadvantaged groups. Early detection and management of anemia during pregnancy can play a vital role in reducing the risk of preterm birth. Strengthening antenatal care services with a focus on nutritional support and community education is essential.